2018
DOI: 10.1002/jcaf.22330
|View full text |Cite
|
Sign up to set email alerts
|

The New Accounting Standard for Revenue Recognition: Do Implementation Issues Differ for Fortune 500 Companies?

Abstract: The purpose of this study is to discover how a sample group of Fortune 500 companies is preparing for adoption of the new revenue recognition standard and how these companies expect it will the impact their current operations. Existing research involved large samples of public and private companies of all sizes. This exploratory investigation seeks to determine if Fortune 500 companies are experiencing different implementation timelines or issues as a result of their size. A survey of chief accounting officers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Despite these warnings, a survey involving CFOs of U.S. technology organizations revealed that 58% had not yet familiarized themselves with the new standards seven months after they were issued (Tysiac & Murphy, 2015). Also, after the first year's deferral, a 2015 PwC survey of 335 respondents found that many organizations do not understand how ASC 606 will affect them, and 38% did not believe ASC 606 will have any significant effect on financial statements (Jonick & Benson, 2018). A December 2015 KPMG poll of nearly 450 financial reporting executives revealed 64% of them were yet to establish a clear ASC 606 implementation plan (Amato, 2015).…”
Section: The Business Practicementioning
confidence: 99%
See 3 more Smart Citations
“…Despite these warnings, a survey involving CFOs of U.S. technology organizations revealed that 58% had not yet familiarized themselves with the new standards seven months after they were issued (Tysiac & Murphy, 2015). Also, after the first year's deferral, a 2015 PwC survey of 335 respondents found that many organizations do not understand how ASC 606 will affect them, and 38% did not believe ASC 606 will have any significant effect on financial statements (Jonick & Benson, 2018). A December 2015 KPMG poll of nearly 450 financial reporting executives revealed 64% of them were yet to establish a clear ASC 606 implementation plan (Amato, 2015).…”
Section: The Business Practicementioning
confidence: 99%
“…A December 2015 KPMG poll of nearly 450 financial reporting executives revealed 64% of them were yet to establish a clear ASC 606 implementation plan (Amato, 2015). Likewise, in 2016 Deloitte reported many organizations had not commenced a formal assessment process for implementing ASC 606 (Jonick & Benson, 2018).…”
Section: The Business Practicementioning
confidence: 99%
See 2 more Smart Citations
“…Enterprises should always pay attention to the contract when using the new revenue standard to determine the measurement of contract revenue. Enterprises should review the contractual information on the books before recognizing revenue [3] .…”
Section: Specific Impact On the Financial Information System Of The E...mentioning
confidence: 99%